Pengaruh Pemberian Pupuk Kalinitra dan Teknik Pemangkasan dengan Sistem Topas Terhadap Pertumbuhan dan Produksi Tanaman Semangka (Citrullus lanatus) - Nurul Nisa Siregar; Syawaluddin Syawaluddin; Imelda Sari Harahap (Jurnal AGROHITA: Jurnal Agroteknologi Fakultas Pertanian Universitas Muhammadiyah Tapanuli Selatan, 2018)
The purpose of this study was to study the effect of Kalinitra fertilizer and pruning techniques on the growth and production of watermelons (Citrullus lanatus). The experimental design used in this study was a Randomized Block Design, with two factors, namely the dose of kalinitra fertilizer (without fertilizer, 100ml, 200ml, 300ml) and pruning techniques (no pruning, topping or topping, trimming tertiary / vine or pruning). The results showed that the application of kalinitra fertilizer showed a significant effect on the age of flowering, fruit diameter, fruit weight per sample and fruit weight per plot. Keywords: Kalinitra, pruning, fruit, flowers